Penerapan Metode Daur Ulang Sampah B3 Rumah Tangga Infeksius Dengan Pendekatan Life Cycle Assessment Melalui Pemberdayaan Masyarakat - Fikri, Elanda; Irmawartini, Irmawartini; Suwerda, Bambang; Wiryanti, Wiwin; Djuhriah, Nany; Hanurawaty, Neneng Yetty; Waluya, Nandang Ahmad (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The prevalence of infectious diseases in Bandung Regency is still very high, in 2020 there were 30,954 cases of diarrhea treated for all ages or 38.06% of the diarrhea discovery target in Bandung Regency. The environmental factor of improper handling of household waste affects 83.3% of the prevalence of diarrhea. Seventy-nine percent of household waste is infectious Household Hazardous Waste (HHW) and is a matter of great concern. Handling of infectious HHW by implementing Clean and Healthy Living Behavior behavior in Bojongsoang Village, Bandung Regency is currently not optimal, so it is hoped that the Bandung Poltekkes Healthy Village Development Program (PPDS) can overcome this problem. The method implemented is to determine the generation of HHW generated by the community so that its impact can be determined using the Life Cycle Assessment (LCA) approach. The impact of  HHW in Bojongsoang Village, Bandung Regency will be resolved through community empowerment using workshops, training and mentoring methods on handling HHW. The implementation of recycling and pyrolysis technology on HHW generated will turn HHW into non-HHW that has more economic value. The results of the activity showed that the generation of HHW obtained at the community service location was 0.010 kg / person / day or about 5.1% of the proportion of domestic waste. The average score of respondents before counseling stages 1 and 2 was 66.03 and 68.73, the score after counseling increased to 77.9 with an interval of 10.1. The results of the training for residents, there was an increase in residents' skills related to sorting, packaging and processing of HHW, from 70 increased to 85 with an interval of 15. The location of the waste bank establishment has been determined based on 4 alternative locations given. The land used in the establishment of the Waste Bank in this PPDS activity was donated by the community from RW.07 Bojong Soang Village, Bandung Regency. The partner group has formed the management of the Bojong Soang Garbage Bank which is a PPDS fostered village. Efforts to apply science and technology in the form of Pyrolysis equipment have been installed in the Bojong Soang Waste Bank, and currently a waste bank has been established in Bojong Soang Village, Bandung Regency.